Food neophobia and enjoyment of tactile play: Associations between preschool children and their parents. (1st February 2016) - Coulthard, Helen; Sahota, Simran
Abstract: A cross-sectional study was conducted to examine whether the relationship between enjoyment of tactile play and food neophobia observed in children (Coulthard & Thakker, 2015) would be related to levels seen in their parents. One hundred and twenty six participants were recruited from playgroup centres in the Walsall area of the West Midlands, UK; 63 children (2–5 years; 30 girls and 33 boys) and 63 attendant parents (53 mothers and 10 fathers). Children and their parents' enjoyment of a tactile play task was rated by both the parent and a researcher, and questionnaire measures of food neophobia and tactile sensitivity were completed by the parent for both themselves and their children. Strong associations were found between parent and child scores across all the measures; food neophobia, tactile sensitivity and tactile play enjoyment. The variables most strongly related to child food neophobia were parental neophobia and enjoyment of tactile play (parent and child). These findings indicate that family resemblance exists not only for food neophobia, but for tactile sensory processing as well, and may represent a possible inherited route to neophobia. The findings strengthen the suggestion that tactile processing is associated with food neophobia although the causal nature of this relationship is still not known.